Consensus guidelines for managing the airway in patients with COVID‐19: Guidelines from the Difficult Airway Society, the Association of Anaesthetists the Intensive Care Society, the Faculty of Intensive Care Medicine and the Royal College of Anaesthetists. (1st April 2020) - Cook, T. M.; El‐Boghdadly, K.; McGuire, B.; McNarry, A. F.; Patel, A.; Higgs, A.
Summary: Severe acute respiratory syndrome‐corona virus‐2, which causes coronavirus disease 2019 (COVID‐19), is highly contagious. Airway management of patients with COVID‐19 is high risk to staff and patients. We aimed to develop principles for airway management of patients with COVID‐19 to encourage safe, accurate and swift performance. This consensus statement has been brought together at short notice to advise on airway management for patients with COVID‐19, drawing on published literature and immediately available information from clinicians and experts. Recommendations on the prevention of contamination of healthcare workers, the choice of staff involved in airway management, the training required and the selection of equipment are discussed. The fundamental principles of airway management in these settings are described for: emergency tracheal intubation; predicted or unexpected difficult tracheal intubation; cardiac arrest; anaesthetic care; and tracheal extubation. We provide figures to support clinicians in safe airway management of patients with COVID‐19. The advice in this document is designed to be adapted in line with local workplace policies. 요약: 코로나 바이러스 감염증 2019 (COVID‐19)를 유발하는 중증 급성 호흡기 증후군‐코로나 바이러스‐2는 전염성이 높다. COVID‐19 환자의 기도 관리는 의료진과 환자에게 중대한 위 험이 된다. 본 가이드라인은 COVID‐19 환자의 기도 관리 원 칙을 개발하여 안전하고, 정확하며, 신속한 수행을 장려하는 것을 목적으로 하였다. 이 합의문(consensus statement)은 COVID‐19 환자를 위한 기도 관리에 대하여 권고하는 짧은 안내문과 함께 제시되었으며, 출판된 문헌 및 임상의와 전문 가로부터 즉시 이용 가능한 정보를 활용하였다. 의료종사자의오염 예방, 기도 관리에 참여할 의료진의 선택, 필요한 훈련 및 장비의 선택에 관한 권고사항이 논의된다. 이러한 환경에 서 기도 관리의 기본적인 원칙이 응급 기관 삽관(emergency tracheal intubation), 예측되거나 예기치 못한 어려운 기관 삽 관, 심정지, 마취 관리, 기관 발관 등의 상황별로 서술된다. COVID‐19 환자의 안전한 기도 관리를 위해 임상의들에게 도 움이 되는 그림들을 제공한다. 이 문서의 권고는 현지 업무현 장 방침(local workplace policies)에 맞추어 조정될 수 있도 록 설계되어 있다.